The Harm in Hate Speech - Waldron, Jeremy (Oliver Wendell Holmes lectures., 2012)
For constitutionalists, regulation of hate speech violates the First Amendment and damages a free society. Waldron rejects this view, and makes the case that hate speech should be regulated as part of a commitment to human dignity and to inclusion and respect for members of vulnerable minorities.